Performance Enhancement of Underwater Wireless Optical Communication Systems using Reconfigurable Intelligent Surfaces - Minah-Eeba W; Bakare B. I. (Advance Research in Communication Engineering and its Innovations, 2026)
Underwater Wireless Optical Communication (UWOC) has emerged as a favorable technology for high-speed underwater data transmission. However, its performance is considerably affected by absorption, scattering, and oceanic turbulence. This study examines the application of Reconfigurable Intelligent Surfaces (RISs) to improve the reliability and efficiency of UWOC technologies. A RIS-assisted UWOC system was deployed and demonstrated using MATLAB and integrating Beer-Lambert attenuation, adaptive phase shift optimization, and Gamma-Gamma turbulence. Monte Carlo simulations were conducted to evaluate the system performance under different channel conditions using parameters such as Bit Error Rate (BER), Signal-to-Noise Ratio (SNR), channel capacity, outage probability, and spectral efficiency. The results showed that the proposed RIS-assisted system achieved a BER of , an SNR of , a channel capacity of , and a spectral efficiency of , overtaking conventional UWOC systems. The outage probability was considerably reduced, showing better-quality communication reliability under turbulent underwater conditions. The findings show that RIS technology effectively mitigate underwater channel impairments and improves signal propagation, making RIS-assisted UWOC a viable solution for future high-speed, reliable, and energy-efficient underwater communication networks supporting marine monitoring, offshore exploration and Internet of Underwater Things (IoUT) applications.